Description of the protocol for the PRACTICAL study: a randomised controlled trial of the efficacy and safety of ICS/LABA reliever therapy in asthma. Issue 1 (29th July 2017) - Fingleton, James; Hardy, Jo; Baggott, Christina; Pilcher, Janine; Corin, Andrew; Hancox, Robert J; Harwood, Matire; Holliday, Mark; Reddel, Helen K; Shirtcliffe, Philippa; Snively, Suzanne; Weatherall, Mark; et al.
Abstract : Introduction: In adult asthma, combination inhaled corticosteroid (ICS)/fast-onset long-acting beta agonist (LABA) used solely as reliever therapy may represent an effective and safe alternative to ICS maintenance and short-acting beta agonist (SABA) reliever therapy. Objective: To compare the efficacy and safety of ICS/fast-onset LABA reliever therapy with ICS maintenance and SABA reliever therapy in adults with asthma. Methods and analysis: A 52-week, open-label, parallel group, multicentre, phase III randomised controlled trial with 1:1 randomisation to either budesonide/formoterol Turbuhaler 200/6 µg, one actuation as required for symptom relief, or budesonide Turbuhaler 200 µg, one actuation twice daily and terbutaline Turbuhaler 250 µg, two actuations as required for symptom relief. 890 adults aged 18–75 years with asthma for whom maintenance ICS and SABA reliever therapy is indicated by current guidelines will be recruited in New Zealand. The primary outcome variable is the rate of severe exacerbations per patient per year. This study will investigate a novel treatment regimen that might lead to a paradigm shift in asthma management for adults for whom guidelines currently recommend maintenance ICS and SABA reliever therapy. Ethics and dissemination: Ethical approval has been granted (15/NTB/178). Study findings will be published according to Iinternational Committee of Medical Journal Editors' recommendations. Trial registration number: ACTRN12616000377437; Pre-results.